Vision Mission of Muhammadiyah University in Indonesia: Ideology Analysis Of Norman Fairclough Approach - SADDHONO, KUNDHARU; ARIANCE LOREN, FABIO TESTY; LATIFAH, LUTFIATUN (Jurnal Studi Pemerintahan, 2017)
Muhammadiyah have features to build the spirit of social and community educa- tion to be more developed and educated. showing the teachings of islam is not just a religion personal and static but dynamic and domiciled as a human life in all aspects. This study attempts to describe and explain the ideology of the vision and mission of Muhammadiyah University in Indonesia using content analysis method. This research is expected to descriptive qualitative research with the critical analysis discourse approach as suggested by Norman Fairclough with the elements that analyzes namely representation, relationships, and the identity.Â The results of the analysis element representation shows that almost all Muhammadiyah University in Indonesia has ideology Islam and Muhammadiyah to be ijtihad and tajdid based on and Muhammad ways. Direction and purpose from which missions made focused on Islamic values. While when viewed from the aspect most many appear on a mission is the as- pect of religiously so further strengthen the statement.